A new ultimate limit state approach to the design of prestressed concrete beams - Hallam, Grant Robert (Concrete Materials and Structural Integrity Research Unit (CoMSIRU), 2016)
The present approach to the design of prestressed beams is antiquated and time consuming. Neither SLS or ULS requirements are satisfied directly. There is a need for a new approach using plastic principles to design the prestressing requirements at ULS considering a whole span at a time, with checks made for SLS requirements afterwards. For a plastic design, the designer would need to know the limits of the bending moment redistribution for the beam under consideration. An equation is therefore necessary to assist the designer in this regard. Such an equation should take into account the cross-section shape of the beam and the prestress to reinforcing steel ratios. Many examples would have to be investigated using a rigorous plastic analysis to formulate such an equation. A computer program has been written as part of this thesis to perform such a rigorous analysis. It's accuracy has been evaluated by comparison with laboratory test beam results. The comparison was favourable, although more results would have to be compared to establish the accuracy that could be expected. A few examples were investigated and the observations noted. Two extreme cases were examined, those of a T-beam and I-beam. The redistribution of bending moments was similar in both cases, but the percentage of the central moment capacity reached was considerably less for the T-beam. For both beams it was impossible to reach the ultimate capacity at the centre before the strain capacity at the supports was exhausted. It was concluded that a plastic design procedure should be introduced, based on the ULS capacity of a span at a time. SLS requirements could then be checked afterwards. This approach would provide a design procedure corresponding to those used for other forms of modern structural design and would be much quicker, safer, more accurate and less costly that the existing design procedures.